Intestinal microbiota of patients with bacterial infection of the respiratory tract treated with amoxicillin - Monreal, Maria Tereza Ferreira Duenhas; Pereira, Paulo Câmara Marques [UNESP]; Lopes, Carlos Alberto De Magalhães [UNESP] (Brazilian Society of Infectious Diseases, 2005)
The intestinal tract harbors a huge diversity of metabolically-active aerobic and anaerobic bacteria that interact, forming a complex ecosystem. This microbiota has an important role in human metabolism, nutrition, immunity, and protection against colonization by pathogenic microorganisms. Several factors can influence the intestinal microbiota; these include age, diet, inflammatory and infectious processes, and the use of antimicrobials. We investigated the influence of bacterial infection of the respiratory tract and of amoxicillin therapy on the normal intestinal microbiota of patients. Bacterial infectious processes affecting the respiratory tract were found to influence the intestinal microbiota, significantly decreasing the number of colony-forming units (CFUs) of Bacteroides spp. and Lactobacillus spp. per gram of feces. The use of amoxicillin also influenced the intestinal microbiota, significantly decreasing the CFU of Bifidobacterium spp. and Lactobacillus spp. /g of feces. Changes in the composition of the intestinal microbiota need to be observed, since a decrease in the normal microorganisms can pose a number of hazards for hosts, including decreased resistance to colonization. With proper follow-up, health-care teams can minimize such hazards by implementing suitable therapy- and diet-related measures, thus reducing the occurrence of detrimental effects on the gastrointestinal ecosystem.
Keywords: Intestinal microbiota; bifidobacterium; bacteroides; lactobacillus